The sustainability of agricultural intensification in the early 21st century: Insights from the olive oil sector in Alentejo (Southern Portugal). - Silveira, A. (2018)
Today Alentejo is witnessing an expansion of strategies (and practices) of agricultural intensification fueled by factors such as a long-standing (political, financial and emotional) investment in the Alqueva irrigation system; national and European policies based on notions of crisis and food security, and global strategies of financial capital enabled by global agricultural trade. In parallel, the large area occupied by the Montado agro-silvo-pastoral system remains important but is facing serious degradation. Its ability to play the diverse economic, social and ecological roles is diminishing despite some support to multifunctional agriculture. Each mode of agricultural production seems to be based on different set of political, social and economic conditions; has different ecological requirements and impacts; and results from the practices of actors with very different conceptions of space and time. Issues to be debate include: Are policies and market incentives supporting agricultural intensification disturbing previously embedded perceptions of space and territory? How? What (re)scaling strategies and practices are assisting the reimagination of territory in the region? Are we witnessing a process of “glocalisation”? Who benefits and loses most from such strategies? What implications do these spatial strategies have for the sustainability of Alentejo social ecological systems and their capacity to adapt to climate change? Montado landscapes and Alentejo´s river systems are adopted as case studies of key socio-ecological systems. Issues of spatiality will be explored using the matrix of socio-spatial relations proposed by Jessop (2008) with emphasis on the political economy of scale and how it is influencing interpretations and enactments of territory. Notions of (re)scaling (Swyngedow 2004) and de/reterritorialisation (Ferrão 2016) will be employed to deepen understandings of emerging socio-spatial relations. Finally, implications of these processes for adaptive capacity in the chosen case studies will be investigated, with the assistance of a range of categories and indicators proposed by Gupta et al. (2010) and Schmidt et al. (2013). References Ferrao 2016 Ruralidades e Território no Capitalismo Contemporâneo: Uma Visão de Longa Duração sobre Portugal Gupta et al. (2010) The Adaptive Capacity Wheel: a method to assess the inherent characteristics of institutions to enable the adaptive capacity of society Schmidt, L., Prista, P., Saraiva, T., O’ Riordan, T., and Gomes, C. (2013). Adapting governance for coastal change in Portugal. Land Use Policy, 31, 314–325. Swyngedouw E (2004) Scaled geographies. Nature, place, and the politics of scale. In: McMaster R, Sheppard E (eds) Scale and geographic inquiry: nature, society and method. Blackwell, Oxford, pp 129–153